A Chinese SCA36 pedigree analysis of NOP56 expansion region based on long-read sequencing - Zou, Jinlong; Wang, Fengyu; Gong, Zhenping; Wang, Runrun; Chen, Shuai; Zhang, Haohan; Sun, Ruihua; Gao, Chenhao; Li, Wei; Shang, Junkui; Zhang, Jiewen (Frontiers in Genetics, 2023)
Spinocerebellar ataxias 36（SCA36）is the neurodegenerative disease caused by the GGCCTG Hexanucleotide repeat expansions in NOP56,which is too long to sequence using short-read sequencing. Single molecule real time (SMRT) sequencing can sequence across disease-causing repeat expansion. We report the first long-read sequencing data across the expansion region in SCA36.We collected and described the clinical manifestations and imaging features of Han Chinese pedigree with three generations of SCA36. Also, we focused on structural variation analysis for intron 1 of the NOP56 gene by SMRT sequencing in the assembled genome.The main clinical features of this pedigree are late-onset ataxia symptoms, with a presymptomatic presence of affective and sleep disorders. In addition, the results of SMRT sequencing showed the specific repeat expansion region and demonstrated that the region was not composed of single GGCCTG hexanucleotides and there were random interruptions. The somatic heterogeneity of SCA36 were verified and described by the perspective of sequencing data. Furthermore, the GGCCTG repeat times is related with the disease progression and age of onset. In conclusion, We extended the phenotypic spectrum of SCA36. We applied SMRT sequencing to reveal the correlation between genotype and phenotype of SCA36.Our findings indicated that long-read sequencing is well suited to characterize known repeat expansion.